Physical and chemical analysis of color glass frit - Diaz Gonzáles, César Raúl (1998)
It has been determined qualitatively and quantitatively , the presence of chemical elements in a sample of imported glass frit yellow , also , some of their physical properties. This conventional techniques were used in both cases , and analysis techniques Fluorescence energy dispersive X -ray (XRF ) and neutron activation analysis ( NAA ), which can detect elements such as zirconium , lead, niobium , arsenic , chlorine , manganese, vanadium , dysprosium , hafnium , barium, and others which are in very low concentration. During the investigation it has been established that the highest averages of the elements present in the sample are silicon , boron , sodium and titanium , and also the color imparted to the frit glass is due to the presence of iron , copper and lead are present as oxides, in the aggregate pigment . We conclude that the technique proves to be effective AAN to quantify up to 30 items and other techniques which must be added to complete the investigation and to compare and analyze their results.